Vplivi okoljskih dejavnikov na prostorsko razporeditev divjega prašiča (Sus scrofa l.) v Sloveniji - Jerina, Klemen (Zbornik gozdarstva in lesarstva, 2006)
Population size and range of wild boar (Sus scrofa L.) have increased significantly during the past decades in Slovenia, as well as in other European countries. Simultaneously, this has caused an increase in agricultural damages. In this study, we examined the influence of various environmental factors on wild boar spatial distribution, and identified its current and potential population distribution range for Slovenia. The researchis based on a large sample (N = 5.977) of georeferenced locations of boar harvested from the entire country and on GIS data layers (25 environmental variables). Analyses revealed that wild boar densities are highest in areas: (a) with outstanding availability of energy-rich food items (i.e. adult deciduous forests with high hard mast production and supplemental feeding places) and good cover accessibility (i.e. agricultural areas near forests and early successional areas); (b) where the temperatures are high andwinters are mild with low snowfall (the probability of use increases with temperature and decreases with quantity of precipitation). Spatial distribution of wild boar also depends on the percentage of forests and the level of forest fragmentation (i.e. size of forest fragments). Currently, boars inhabit 55% of Slovenia, yet the potential habitat extends up to 67% of the country. The wild boar population size and range are therefore likely to increase, especially if the current trends of environmental changes continue, such as rising temperatures, increased forested area, and a decrease in coniferous trees.
Keywords: divji prašič; habitati; okolje; razširjenost; Slovenija; vplivi